Development of a core set from a large rice collection using a modified heuristic algorithm to retain maximum diversity - Chung, Hun-Ki; Kim, Kyu-Won; Chung, Jong-Wook; Lee, Jung-Ro; Lee, Sok-Young; Dixit, Anupam; Kang, Hee-Kyoung; Zhao, Weiguo; McNally, Kenneth L.; Hamilton, Ruraidh S.; Gwag, Jae-Gyun; Park, Yong-Jin (Wiley, 2009)
A new heuristic approach was undertaken for the establishment of a core set for the diversity research of rice. As a result, 107 entries were selected from the 10 368 characterized accessions. The core set derived using this new approach provided a good representation of the characterized accessions present in the entire collection. No significant differences for the mean, range, standard deviation and coefficient of variation of each trait were observed between the core and existing collections. We also compared the diversity of core sets established using this Heuristic Core Collection (HCC) approach with those of core sets established using the conventional clustering methods. This modified heuristic algorithm can also be used to select genotype data with allelic richness and reduced redundancy, and to facilitate management and use of large collections of plant genetic resources in a more efficient way.